Pendampingan Baca Tulis AlQuran Anak melalui Metode Qiroati di Masjid Al-Barkah Kota Padang - Putra, Elfi; Kustati, Martin; Gusmirawati, Gusmirawati (Al-DYAS, 2023)
The lack of public awareness of Alquran reading and writing education is marked by an imbalance between teachers and students in learning to read and write the Alquran at the Al-Barkah Mosque in Padang City so that learning outcomes do not go as desired, assistance in reading and writing Alquran -Qur'an aims to measure the extent to which Ustadz and Ustadzah provide understanding to Alquran educational park students in reading the Alquran and writing correct Alquranic verses according to the rules, from the way of reading, rhythm, and know the tajwid contained in the reading. The methods used in this assistance are interviews and documentation, the methods used in reading the Alquran are repetition, question and answer, deepening the material and writing verses. students who are taught at the Alquran educational park at primary school level, the aim of this assistance is to measure the extent of the ability of Alquran educational park children in reading the Alquran at the Al-Barkah Mosque in Padang City by applying the qiroati method, children know and understand how to read the Alquran correctly with tartil rhythm. The application of the Qiroati method has a significant role in learning to read and write the Alquran at the Al-Barkah Mosque in Padang City.